Competition among Colleges for Students across the Nation. (18th November 2017) - Smith, Jonathan; Pender, Matea; Howell, Jessica
Abstract : Colleges compete with one another for students. This article overcomes historical data limitations associated with forming a national picture of competition among colleges using the universe of SAT‐takers. We identify and measure competition by the overlap within the set of colleges to which students send their SAT scores (Score Sends). We document the competitive landscape for 1152 colleges between 1996 and 2013 including the number of competitors, the intensity of the competition, and characteristics of a college's primary competitors. For example, on average, a college has Score Send overlap with 736 other institutions and their primary competitors are located 104 miles away and have 34.2% Score Send overlap. All of the documented measures of competition vary greatly by institution type but do not change dramatically over the time period examined.